Power body - Seabourne, Tom (YMAA, 1994)
A resource book aimed at any martial artist. Sports psychologist and twice US Taekwondo champion Tom Seabourne explains how to achieve peak performance with meditation, relaxation and breathing techniques. Readers discover how to improve fat loss, muscle building and fatigue control.